ANALISIS TIPOLOGI LEPIDOPTERA BERDASARKAN OBSERVASI HABITAT DI KAWASAN HUTAN LINDUNG NUSAKAMBANGAN, CILACAP, JAWA TENGAH - Sari, Dwi Arum; Cahyani, Kurnia; Ardhiansyah, Muhammad Anand; Purnomosidi, Aziz (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Abstract- The objectives of this research are (1) to know abiotic component in Nusakambangan Island, (2) to know preferency ofÂ  habitat inclination Lepidoptera in Nusakambangan Island (3) to know the diversity of Lepidoptera in Nusakambangan Island.This is descriptive qualitative research. Method that used in this reseacrh consist of several stages; (1) determine observation location,(2) gathering data of abiotic and veegetation habitat of Lepidoptera, (3) gathering data of Lepidoptera composition. The result show that faound 52 species from 3 family, there are Papilionidae, Pieridae, Nymphalidae, 1 superfamiliy Hesperidae dan 1 subfamily Polyommatinae. There are 22 unidentified butterflies until species level. Habitat preference are influenced by many factors. The factors are abiotic and biotic factor. Abiotic factors include humidity, light intensity, and air temperature. For biotic factors include the of flower types, host plants.Â Keywords: tipology, preferencyi habitat, lepidoptera, Nusakambangan island